EU environmental governance: Uncomplicated and predictable policy making? By Jenny Fairbrass and Andrew Jordan - Jenny Fairbrass; Andrew Jordan (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2002)
Based on studies of the reform of the European Union's (EU's) structural funding programmes, some scholars consider the EU to be a disordered, complex and multi-layered polity. According to such a perspective, shifting and contested power relationships in the EU, resulting in the dispersal of decision-making authority among different tiers of governance, have produced some loss of control over policy development among member states' national executives. Critics dismiss these claims on the basis that structural funding is intrinsically distributive and, therefore, inherently pluralistic. By contrast, in this paper we examine aspects of a regulatory policy area (i.e. environmental policy) to see how it has unfolded in the United Kingdom (UK) over a thirty-year period, unveiling the activities of both government and non-governmental (NGOs) actors. The data suggest that UK-based environmental groups who were previously marginalised in the national arena have adapted their behaviour to establish direct relations with EU level policy-makers and channel their demands via European-wide and international groups. This approach has enabled the UK groups to press for environmental policy outcomes that were not likely to have been secured had they relied solely on pursuing their objectives with or via national policy-makers. That the entrepreneurial activities of supranational actors have been a major source of unintended and unwelcome consequences for the UK government is also evident. Our evidence suggests that environmental decision-making in the EU is unpredictable, confused, intricate and multi-centred and not entirely within the control of member states' national executives.
Keywords: 330; biodiversity; European Union; land use planning; multi-level governance; Biodiversität; EU-Staaten; EU-Umweltpolitik; Politische Entscheidung